A Brazilian Response to 20th Century School Infrastructure Planning - Bueno Chahin, Samira (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
Taking school spaces as an interdisciplinary issue encompassing the fields of education, architecture, and urbanism/urban planning, this article gathers theoretical and technical references from among these disciplines throughout the first half of the 20th century in order to locate possible exchanges carried out by Anísio Teixeira while shaping his Park-school, Class-schools program. The argument rests on the reading of documents taken from a variety of circumstances in his career as an educational administrator, even though not necessarily produced by him. The aim is to encourage a debate regarding a Brazilian response to the international challenge of providing a spatial infrastructure consistent with a modern school program.